The Influence of VAT Variation on the Damages Resulting From Fraud in the Romanian Economy - Miron, Gabriela Monica (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The purpose of this article is to determine the influence of the VAT rates variation, on different fields of activity of national economy, on the damage caused to the state's consolidated budget, from the point of view of the damage caused and damage recovered the damage that is caused by economical-financial offenses. Between 2011 and 2019, the VAT rate registered a continuous decrease from 24% to 19%, which significantly reduces the amount of damage caused and recovered. Our study intends to point out the fact that in Romania, the various VAT rate had a major income on the damage caused as well as the damage recovered, thus leading to a decrease in several fields of activity. On the opposite side, there were fields of activity where a major increase of damage was registered, considering that the VAT rate decreased all along the period of time analyzed, such is the case of recycled materials. In some cases, the VAT decrease determined significant diminution of the damage caused and not of the damage recovered and in other cases, it had an effect only on the damage recovered or had no effect at all.